Study Of The Effect Of Aluminum Content And C / S Ratio On The Physico-mechanical And Thermal Properties Of A Lightweight Concrete Made From Sand Dune - Damene, Z.; Goual, M. S.; Saiti, I.; Benhassine, N.; Ferhat, A. (University of Eloued جامعة الوادي, 2014)
This research is a contribution to the development of local materials especially in the development of a cellular concrete with dunes sand. This is an experimental study whose objective is to see the influence of the C/S (dosage of cement compared to sand) and the dosage of aluminum on the physico- mechanical and thermal performance of lightweight concrete cellular type. The results showed that the cement compared to the sand has a remarkable effect on the reaction and that on expansion the mechanical behavior as well as the dosage of aluminum in the composition of cellular concrete has a certain threshold Aluminium beyond which provides no relief benefits. Based on these results, the cellular concrete made from sand dune can be classified as light structural concrete with insulation suitable for very hot and arid environment of our region power.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 02
Keywords: Valorisation; Cellular concrete; Dune sand; Aluminium; mechanical properties; thermal insulation.